Performance evaluation of routing protocols in live video streaming over wireless mesh networks - Barekatain, Behrang (Penerbit UTM Press, 2013)
In recent years, live video streaming over Wireless Mesh Networks (WMNs) has been of great interest among users. However, node mobility, interferences and competition for the available resources are some important factors, to name a few, which can considerably affect the perceived video quality on wireless nodes. In this regard, employing an efficient routing protocol can address these challenges as much as possible. The fact of the matter is that the real performances of the most recently used routing protocols in live video streaming over WMNs is remaining as an open issue. Therefore, this study designs and implements a simulator using the OMNET++ framework and measure the performances of these routing protocols under various and different network conditions based upon the different performance metrics. To the best of our knowledge, this is the first study which precisely and comprehensively performs this evaluation. The obtained results not only do help interested researchers to select the most appropriate routing protocol for their proposed video streaming applications over WMNs, but also let them introduce more efficient hybrid protocols based upon the considered routing protocols in this study.